Composition of Different Carbohydrate Fractions in Potatoes: Effect of Cooking and Cooling. (3rd June 2021) - Raigond, Pinky; Parmar, Vandana; Thakur, Asha; Lal, Milan Kumar; Changan, Sushil Sudhakar; Kumar, Dharmender; Dutt, Som; Singh, Brajesh
Abstract: Effect of cooking methods (boiling, microwaving, pressure cooking) and storage conditions (–20, 4, 12 °C) on resistant starch (RS), amylose, and sugars in the Indian cultivars, viz., Kufri Pukhraj and Kufri Chipsona‐1 is investigated. Starch decreased significantly in Kufri Pukhraj and non‐significantly in Kufri Chipsona 1 with a concomitant significant increase in reducing sugars and sucrose in cooked potatoes. Storage of microwaved tubers at 4 °C for 48 h results in 4–6% reduction in starch content with 66–109% and 16–18% increase in reducing sugars and sucrose, respectively. Increase in RS content at –20, 4 and 12 °C after 48 h is 14%, 21%, and 27% after microwaving, 12%, 25%, and 23% after boiling, and 13%, 15%, and 20%, respectively, after pressure cooking. Amylose showed high positive correlation with RS at 4 °C (R = 0.756) and 12 h storage (R = 0.924). The study reveals that storage of microwaved potatoes at 12 °C for 48 h increases the RS to a higher extent, therefore, these cooking and storage conditions may be used by potato consumers. Due to inverse relation of RS and amylose with glycemic index they can be used for indirect estimation of glycemic index. Abstract : Storage of microwave cooked potatoes at 4 °C for 48 h results in 4–6% reduction in starch content with concomitant increase in reducing sugars (66–109%) and sucrose (16–18%). Storage of microwaved potatoes at 12 °C for 48 h increases the resistant starch concentration to the higher extent, therefore, these cooking and storage conditions may be used by potato consumers.